2012
DOI: 10.1038/mt.2011.249
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Gene Therapy for Parkinson's Disease Using Astrocytes as Hosts for Localized Neurotrophic Factor Delivery

Abstract: Current gene therapy approaches for Parkinson's disease (PD) deliver neurotrophic factors like glial cell line-derived neurotrophic factor (GDNF) or neurturin via neuronal transgene expression. Since these potent signaling-inducing neurotrophic factors can be distributed through long-distance neuronal projections to unaffected brain sites, this mode of delivery may eventually cause side effects. To explore a localized and thus potentially safer alternative for gene therapy of PD, we expressed GDNF exclusively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
88
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 50 publications
3
88
0
1
Order By: Relevance
“…Its role in neuronal metabolism and its neuroprotective profile has been well established (Airaksinen and Saarma, 2002;Broome et al, 1999;Drinkut et al, 2012;Kordower and Bjorklund, 2013;Moran and Graeber, 2008). Long-lasting analogues of GDNF are currently under investigation as a potential treatment of PD (see eg.…”
Section: Discussionmentioning
confidence: 99%
“…Its role in neuronal metabolism and its neuroprotective profile has been well established (Airaksinen and Saarma, 2002;Broome et al, 1999;Drinkut et al, 2012;Kordower and Bjorklund, 2013;Moran and Graeber, 2008). Long-lasting analogues of GDNF are currently under investigation as a potential treatment of PD (see eg.…”
Section: Discussionmentioning
confidence: 99%
“…One of the promising approaches to achieve this is to search for an endogenous system locally producing neurotrophic factors in brain and/or small molecules that can activate this endogenous system producing neurotrophic factors by passing through the blood-brain barrier. Furthermore, neurotrophic factor use is a safer and efficient gene therapy when expressed in astrocytes compared to its expression in neurons in MPTP and 6-OHDA models of Parkinson's disease (Drinkut et al, 2012). Taken together, astrocytic TRPV1-derived endogenous CNTF production by capsaicin described in our current data has the in vivo neuroprotective properties both in toxin (MPP + )-or gene-(-synuclein, SNCA) based models of Parkinson's disease, suggesting that this endogenous system producing CNTF in astrocytes can overcome the substantial problems for clinical application of neurotrophic factors and might be a promising therapeutic target for the treatment of Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Various Parkinson's disease animal models generated by administration of toxins including 1-methyl-4-phenylpyridinium (MPP + ) (Park et al, 2012), 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) (Chung et al, 2010), or 6-hydroxydopamine (6-OHDA) (Drinkut et al, 2012) orsynuclein over-expression through viral transduction in rats and genetic methods in mice (Kirik et al, 2002;Chesselet, 2008;Decressac et al, 2012) have been used to identify therapeutic targets and test disease-modifying therapies. Although little is known about the cause of Parkinson's disease, major concerns include the loss of dopamine neurons and the subsequent depletion of striatal dopamine, which causes motor abnormalities such as resting tremor, bradykinesia and rigidity (Dauer and Przedborski, 2003;Savitt et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This PD model is superior for use in the present study on the effects of gastrodin on PD. Accumulating data have indicated the importance of astrocytes in Parkinsonism (15)(16)(17). It has also been demonstrated that several connexins are expressed in neurons and astrocytes, and these may be involved in the release of ATP and glutamate (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that several connexins are expressed in neurons and astrocytes, and these may be involved in the release of ATP and glutamate (18)(19)(20)(21). In addition, astrocytes have been shown to be involved in neurological disorders, including PD (15,16), and astrocyte gap junctions may be formed of multiple connexins (22). The metabolic and ionic coupling provided by these diverse types of gap junctions may provide intercellular signaling required for brain development and cortical lamina-tion (19).…”
Section: Introductionmentioning
confidence: 99%